Urological Injuries Following Obstetric and Gynecological Surgeries - Robbani, ABM Golam; Ashraf, Fatema; Akhtar, Hasina; Mostanzid, SM (TAJ: Journal of Teachers Association, 2009)
Obstetric and gynecological surgeries are not uncommon cause of iatrogenic injury to the urinary tract. In this study, we retrospectively report our experiences with these injuries over the last 8 years. Between January-2000 and December-2008, 80 female with age range of 21 to 65 years, presented to us with various urological injuries following obstetric or gynecological surgeries. The types of injury were as follows: vesico-vaginal fistula (56), uretero-vaginal fistula (14), unilateral ureteral ligation (5), bilateral ureteral ligation (2), ureteral trans-section (2), and vesico-uterine fistula (1). In this series, all patients of urological injuries due to obstetric or gynecological surgery were cured of their complications and were free of any complain related to the procedures, except 3 cases of VVF who experienced a failed initial repair. They were managed successfully by 2nd surgery. Injury may occur during obstetric and gynecological surgeries to the urinary tract. This iatrogenic injury imposes a great impact on physical and mental conditions of the patient and her family. Therefore, it is mandatory for the gynecologists and obstetricians to pay careful attention to the anatomy of the urinary tract in order to avoid such iatrogenic injuries. doi: 10.3329/taj.v21i2.3793 TAJ 2008; 21(2): 135-139